2017
DOI: 10.1002/gj.2904
|View full text |Cite
|
Sign up to set email alerts
|

Surface uplift of the Central Yunnan Plateau since the Pliocene

Abstract: The Central Yunnan Plateau (CYP) is located in the southeastern end of the Sichuan‐Yunnan rhombic block. CYP is surrounded by the South China Block to the east and the Indo‐China Block to the southwest. Stratigraphy and topography research shows the relative surface uplift of the CYP since the Pliocene. However, the widely accepted model of lower crustal flow is very difficult to fully explain the surface uplift of CYP, with faults and fold structures in the brittle shallow crust. The lower crust thickening le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…However, all three estimates indicated that the population demography of Q. acutissima most likely determined by major tectonic events and paleoclimate oscillations during Pliocene–Pleistocene. For example, the surface uplift of the Yunnan‐Guizhou Plateau during the Pliocene (Li et al, 2018) could have created physical barriers that prevented inter‐regional gene flow between mountainous West China and low‐lying East China, leading to east–west divergence in Q. acutissima . In addition, the intensification of monsoon in East Asia during the Pliocene (An et al, 2001; Ao et al, 2016; Yang et al, 2018) could have increased the climatic differences between West and East China, facilitating ecological selection‐driven genetic divergence.…”
Section: Discussionmentioning
confidence: 99%
“…However, all three estimates indicated that the population demography of Q. acutissima most likely determined by major tectonic events and paleoclimate oscillations during Pliocene–Pleistocene. For example, the surface uplift of the Yunnan‐Guizhou Plateau during the Pliocene (Li et al, 2018) could have created physical barriers that prevented inter‐regional gene flow between mountainous West China and low‐lying East China, leading to east–west divergence in Q. acutissima . In addition, the intensification of monsoon in East Asia during the Pliocene (An et al, 2001; Ao et al, 2016; Yang et al, 2018) could have increased the climatic differences between West and East China, facilitating ecological selection‐driven genetic divergence.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, Gln has no significant effect on callus induction, which may be due to the low concentration of the addition, no obvious effect was observed. Hydrolyzed casein (CH) is a kind of plant nutrition additive, which can promote the growth and differentiation of callus [17,18]. In this study, it was found that high concentration of CH could inhibit the growth of callus.…”
Section: Discussionmentioning
confidence: 99%
“…However, the western branch of the LVZs shows a southward extrusion nearly along the ASRR, and further extends into the north-eastern corner of the ICB across the ASRR (Figure 6a; Bao et al, 2015). Considering the upper-middle crustal motion revealed by GPS station velocities and P axes, the uppermiddle crust and lower crust beneath the areas of the two LVZ branches in the CDB are strongly decoupled (Figure 6a; Li et al, 2018), which is also supported by the lithospheric rheological structures of a rather weak crème brûlée regime beneath the CDB (Figure 6e; Gong et al, 2018). The leading role of the two branches of the LVZs for tectonic uplift has been shown in profiles L1-2, L2-1, L4-3, and L5-1 nearly along a N-S direction (Figures 4 and 5).…”
Section: Key Factors Responsible For Tectonic Upliftmentioning
confidence: 99%
“…The ASRR stands out as a remarkable boundary fault in morphology and geology, and involves two stages: the 500-700 km sinistral slip in the Tertiary (34-17 Ma), and the reactive 5.3-57 km dextral slip in the Quaternary (5 Ma;Harrison et al, 1996;Leloup et al, 1995;Searle, 2006). With the resistance of the SCP, part of the dextral displacement along the ASRR is converted to a large-scale S-N trending syncline and anticline, known as the Chuxiong Basin and CYP (Figure 1; Li et al, 2018;. The E-W extension occurring at the top of the S-N trending anticline is indicated by a series of grabens and horsts along the XJFZ (such as Dianchi Lake and Fuxian Lake in Figure 1), with Proterozoic fold basements and Palaeozoic rocks exposed in the central part, and Mesozoic continental strata in the east and west (Wang et al, 1998;.…”
Section: Geological Backgroundmentioning
confidence: 99%
See 1 more Smart Citation